The Learning Research and Development Center at the University of Pittsburgh - Yeager, John L.; Glaser, Robert; Pittsburgh Univ., PA. Learning Research and Development Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
The Learning Research and Development Center, an institute composed of faculty from the University of Pittsburgh, has as its general purpose the scientific study of the problems of learning and instruction. Particular attention is given to the nature of the educational and psychological environment required to maximize the potential of the individual learner. The Center's activities range from basic theoretical studies of the learning process; through the development of procedures, materials and equipment of instruction; to the development of educational programs in school settings. The four major programs described are (1) Basic Learning Studies, (2) Computer-Assisted Instruction Studies, (3) Field Research, and (4) Experimental School Development. For each of the major programs, one or two illustrative projects are describes: (1) language comprehension skills and response latency characteristics in learning, (2) curriculum design for computer-assisted instruction, (3) computer management of individualized instruction and studies of learning rate and (4) experimental school operations concerned with individually prescribed instruction and curriculum design in early learning. (Author/LS)
Contract Number: OEC-3-16-043.
ERIC Note: Preprint of an article to appear in The Journal of Research and Development in Education, Fall, 1968.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Education; Educational Programs; Learning Resources Centers; Learning; Computer Assisted Instruction; Educational Research; Innovation; Learning Processes; Research